2016
DOI: 10.1111/jph.12524
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Inoculants with Multifaceted Traits Suppress Rhizoctonia Populations and Promote Plant Growth in Cotton

Abstract: The suppressive effects of microbial inoculants on cotton seedling mortality were assessed in Rhizoctonia solani‐infested soil. Per cent mortality ranged from 16 to 32 (60–120 days after sowing, DAS) and significant differences were recorded at 120 DAS, especially after drenching with compost tea of Azotobacter sp. and Anabaena torulosa—Trichoderma viride‐biofilmed formulations. The activity of hydrolytic enzymes was reduced in diseased root tissues due to a majority of the microbially inoculated treatments, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Chickpea Novel cyanobacterial and biofilmed inoculants enhanced plant growth and yields [267] Chickpea Mesorhizobium ciceribased biofilms showed plant growth promoting and antifungal activity [243] Chrysanthemum Anabaena and Trichoderma based biofilms improved soil fertility attributes under protected cultivation [265] Cotton Mucilage of cyanobacteria offer a favorable environment for several bacterial biofilms, which were developed and characterized for their plant growth promoting and fungicidal traits [232,233] Cotton Optimization of process for biofilm development using Trichoderma as a matrix and agriculturally important bacteria (Azotobacter chroococcum, Pseudomonas fluorescens, and Bacillus subtilis) as partners and reported positive effects of these multi-species biofilms on plant growth promoting traits [237,238] Cotton Trichoderma and Anabaena based bacterial biofilms controlled Macrophomina phaseolina infected crop along with plant growth promotion [260] Cotton Significance of varietal responses in cotton in relation to the efficacy of cyanobacterium and Trichoderma based biofilms and their establishment in the rhizosphere [261] Cotton Microbial inoculants with multifaceted traits suppress Rhizoctonia populations and promote plant growth [264] Cyanobacterial based bacterial and fungal biofilms control phytopathogenic fungi and nematodes [233] Lettuce Fungal-bacterial biofilms inoculation aid in breaking seed dormancy and improve germination of seeds and plant productivity [271] Maize Fungal-bacterial biofilms inoculation coupled with 50% chemical fertilizer enhanced microbial diversity [273] Maize Fungal-bacterial biofilms differ from bacterial monocultures in regulating improved seed germination and plant growth [272] Maize Cyanobacteria-based bioinoculants showed positive influence on growth and yields [263] Mungbean, Soybean…”
Section: Major Findings Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chickpea Novel cyanobacterial and biofilmed inoculants enhanced plant growth and yields [267] Chickpea Mesorhizobium ciceribased biofilms showed plant growth promoting and antifungal activity [243] Chrysanthemum Anabaena and Trichoderma based biofilms improved soil fertility attributes under protected cultivation [265] Cotton Mucilage of cyanobacteria offer a favorable environment for several bacterial biofilms, which were developed and characterized for their plant growth promoting and fungicidal traits [232,233] Cotton Optimization of process for biofilm development using Trichoderma as a matrix and agriculturally important bacteria (Azotobacter chroococcum, Pseudomonas fluorescens, and Bacillus subtilis) as partners and reported positive effects of these multi-species biofilms on plant growth promoting traits [237,238] Cotton Trichoderma and Anabaena based bacterial biofilms controlled Macrophomina phaseolina infected crop along with plant growth promotion [260] Cotton Significance of varietal responses in cotton in relation to the efficacy of cyanobacterium and Trichoderma based biofilms and their establishment in the rhizosphere [261] Cotton Microbial inoculants with multifaceted traits suppress Rhizoctonia populations and promote plant growth [264] Cyanobacterial based bacterial and fungal biofilms control phytopathogenic fungi and nematodes [233] Lettuce Fungal-bacterial biofilms inoculation aid in breaking seed dormancy and improve germination of seeds and plant productivity [271] Maize Fungal-bacterial biofilms inoculation coupled with 50% chemical fertilizer enhanced microbial diversity [273] Maize Fungal-bacterial biofilms differ from bacterial monocultures in regulating improved seed germination and plant growth [272] Maize Cyanobacteria-based bioinoculants showed positive influence on growth and yields [263] Mungbean, Soybean…”
Section: Major Findings Referencesmentioning
confidence: 99%
“…In maize hybrids, cyanobacterium based bacterial biofilmed formulations act as plant‐growth‐promoting agents and save nitrogenous fertilizer inputs . In cotton, inoculation of novel microbial biofilm inoculants helped to suppress Rhizoctonia population in soil . Under ptotected cultivation system, microbial biofilm inoculation improved Chrysanthemum growth and yield apart from enhancing soil fertility .…”
Section: Agriculturally Important Microbial Biofilmsmentioning
confidence: 99%
“…However, genera such as Cylindrospermum sp., Synechococcus sp., Aulosira sp., Scytonema sp., Tolypothrix sp., Westiellopsis sp., Calothrix sp., Phormidium sp., and Oscillatoria sp. are also included in the reports (Figure 3) [4,29,31,38]. A study conducted by [20] reports the capacity of two cyanobacteria isolates, identified as Anabaena sp.…”
Section: Discussionmentioning
confidence: 99%
“…To isolate and identify native plant-growth-promoting cyanobacterial strains in wheat and rice crops [4,[32][33][34][35][36]. To determine the effectiveness of cyanobacteria colonization, their physical, metabolic and enzymatic effects, as well as their impact as biofertilizers in stressed soils, corn, and rice crops [17,[37][38][39][40].…”
Section: Action Mechanisms Of Cyanobacteria With Pgpr or Pgpmentioning
confidence: 99%
“…Moreover, they improve the soil's water retention capacity and prevent eutrophication which enhances plant growth [19]. Positive effects of plant growth due to cyanobacterial inoculation have been reported for crops like rice [27,28], maize [29], cotton [30], wheat [6,7], peas [31] and tomatoes [32–34].…”
Section: Introductionmentioning
confidence: 99%